A Randomized Controlled Trial Comparing Injection Polidocanol, with Injection 50% D/W in Rectal Prolapse - Umair Khaliq Siddiqi, Muhammad Sharif, Hafiz Muhammad Adnan, Hafiza Mariam Rafiq, Muhammad Kashif Bashir, Hamza Malik, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Rectal prolapse manifests as the protrusion of the rectal mucosa through the anal opening. There can be partial or full thickness prolapse. It usually occurs before 4 years of age. Rectal prolapse in childhood tends to affect both males and females equally. Aim: To compare Inj. Polidocanol with Inj 50% D/W in rectal prolapsed in this randomized controlled trial. Methods: The study was conducted in the pediatric surgical ward of Mayo Hospital & King Edward Medical University Lahore, after receiving approval from the Hospital's Ethical Committee. There were 60 patients rectal prolapse with 30 patients in each group. Polidocanol was used in group A while 50%dextrose water was used in group B. The procedure was performed under general anesthesia. In the postoperative period children were observed for early complications like fever, anaphylaxis, diarrhea, hemorrhage, pain while defecating, mucosal edema and constipation. Results were analyzed with SPSS. Results: Out of 60, 36 were male while 24 were female. Group A included 16 male and 14 females whereas group B had 20 males and 10 female children. Mean age was 5.35years with SD of 2.7 and ranging from youngest child of 8 months till eldest of 12 years. In group A mean age was 5.44 while mean age of group B was 5.26 years. All 30 patients in group A were relieved of their symptoms after single session of Polidocanol so giving 100% of success rate while 28 patients (93.33%) in group B were relieved of their symptoms while 2(6.66%) patients developed recurrence with no significant difference. The complications observed in the study were post-operative constipation in 3(10%) patients in group A, however no patient developed postoperative stricture, infection or adverse drug reaction. In group B no patient developed any post-operative complication. Practical Implication: This comparative study helps us to find more effective and better drug available as a sclerosing agent to treat rectal prolapse in pediatric population. It’s also cost effective and with fewer side effects and easily available. Conclusion: In conclusion, injection sclerotherapy using polidocanol emerges as an equally successful procedure for managing RP in children. This medication demonstrates enhanced efficacy, safety, and accessibility. The process is not only less time-consuming but also entails minimal complications. Keywords: Rectal Prolapse Manifests, Protrusion, Mucosa, Chronic Constipation, Hirschsprung’s Disease,